2012
DOI: 10.1002/mrm.24168
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle 1H MRSI before and after prolonged exercise. I. muscle specific depletion of intramyocellular lipids

Abstract: Aim of the study was to determine distribution and depletion patterns of intramyocellular lipids (IMCL) in leg muscles before and after two types of standardized endurance exercise. ¹H-magnetic resonance spectroscopic imaging was performed (1) in the thigh of eight-trained cyclists after exercising on an ergometer for 3 h at 52 ± 8% of maximal speed and (2) in the lower leg of eight-trained runners after exercising on a treadmill for 3 h at 49 ± 3% of maximal workload. Pre-exercise IMCL contents were reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…After acute exercise at moderate intensity, most studies report not only a decrease in IMCL in healthy and sedentary subjects (Bucher et al, 2014;Decombaz et al, 2001;Egger et al, 2013;SchrauwenHinderling et al, 2003a;White et al, 2003) but also in endurancetrained athletes (Brechtel et al, 2001b;De Bock et al, 2007;Decombaz et al, 2001;Johnson et al, 2003;Krssak et al, 2000;Rico-Sanz et al, 2000;van Loon et al, 2003a;van Loon et al, 2003b;Vermathen et al, 2012;Zehnder et al, 2005). Importantly, the utilization of IMCL during exercise depends upon the duration and intensity of exercise and the training status of the participant.…”
Section: Effects Of Acute Exercise On Imclmentioning
confidence: 99%
See 1 more Smart Citation
“…After acute exercise at moderate intensity, most studies report not only a decrease in IMCL in healthy and sedentary subjects (Bucher et al, 2014;Decombaz et al, 2001;Egger et al, 2013;SchrauwenHinderling et al, 2003a;White et al, 2003) but also in endurancetrained athletes (Brechtel et al, 2001b;De Bock et al, 2007;Decombaz et al, 2001;Johnson et al, 2003;Krssak et al, 2000;Rico-Sanz et al, 2000;van Loon et al, 2003a;van Loon et al, 2003b;Vermathen et al, 2012;Zehnder et al, 2005). Importantly, the utilization of IMCL during exercise depends upon the duration and intensity of exercise and the training status of the participant.…”
Section: Effects Of Acute Exercise On Imclmentioning
confidence: 99%
“…Furthermore, it was shown that a HFD increased net IMCL degradation during exercise, an effect that was not altered by an exercise training program (Van Proeyen et al, 2011), again possibly owing to increased basal IMCL values. Indeed, several studies indicate that it may be basal IMCL values that are the determinant of IMCL usage during exercise (Steffensen et al, 2002;Vermathen et al, 2012;Zehnder et al, 2006), so higher IMCL levels at the onset of exercise may result in higher IMCL utilization. For example, athletes given 1.5 days of lipid supplementation before an acute cycling exercise showed increased pre-exercise IMCL levels; the IMCL depletion during exercise was strongly correlated with these preexercise IMCL levels (Zehnder et al, 2006).…”
Section: Effects Of Acute Exercise On Imclmentioning
confidence: 99%
“…Vermathen et al (46) investigated IMCL levels in 13 different muscles, including VL, SOL, and TA, before and after aerobic exercise. They found that baseline IMCL levels for different subjects were strongly correlated between the muscle (average correlation coefficient between all muscle was r ϭ 0.83).…”
Section: E38 Imcl and Gene Expression In Muscle After High-fat Dietmentioning
confidence: 99%
“…The reduction of IMCL contamination was achieved by using smaller voxel sizes and by a post-acquisition selection of voxels with acceptable separation of IMCL CH2 line from EMCL CH2 . Conventional STEAM, PRESS or slice selective 2D MRSI techniques reached nominal voxel sizes 5×5×10 mm 3 using spatial matrices 32×32 or 36×36 [11][15]. Acquisition time was 20–35 minutes.…”
Section: Introductionmentioning
confidence: 99%